Incidence of nephrolithiasis after bladder augmentation in people with spina bifida. Issue 4 (August 2021) - Salama, Amr K.; Misseri, Rosalia; Hollowell, Nathan; Hahney, Brittany; Whittam, Benjamin; Kaefer, Martin; Cain, Mark P.; Rink, Richard C.; Szymanski, Konrad M.
Summary: Introduction: Risks of nephrolithiasis after bladder augmentation in people with spina bifida (SB) remain unclear. Annual incidence of nephrolithiasis in the general population is 0.01% for 10–14 years old, 0.07% for 15–19 years old and 0.2% for 20–24 years old. Our aim was to assess the incidence and risk factors of nephrolithiasis in SB patients after augmentation. Methods: Patients with SB and augmentation followed at our institution were retrospectively reviewed (born ≥1972, surgery 1979–2019). Patients were screened annually with renal bladder ultrasound and abdominal radiograph. Main outcome was nephrolithiasis treatment. Kaplan–Meier survival and Cox proportional hazards analysis were used. Possible predictors were assessed using stepwise forward selection (variables with p < 0.1 on univariate analysis included in multivariate analysis). Results: 427 patients with SB and augmentation were included (51.8% female, 74.9% shunted). Median age at augmentation was 8.5 years (median follow-up: 12.4 years, ileum segment: 81.0%, bladder neck procedure: 60.7%, urinary channel: 74.2%) and 28.8% developed bladder stones. Overall, 47 (11.0%) patients were treated for nephrolithiasis. After correction for differential follow-up, nephrolithiasis was treated in 7.3% at 10 years, 13.2% at 15 years, and 18.0% at 20 years (Figure ). Patients presented with either a urinary tract infection (46.8%), on screening (44.7%), or pain (8.5%). Stones were treated percutaneously, endoscopically or by ESWL (63.8%/34.0%/10.7%, respectively). Most were calcium stones (58.3%). On multivariate analysis, compared to younger patients, patients augmented at ≥10 years of age had 1.84 times the risk of nephrolithiasis (p = 0.01). Nephrolithiasis was more common in those who developed bladder stones (HR = 3.00, p < 0.0001). Among those with both renal and bladder stones, bladder stones typically preceded nephrolithiasis (55.2%), were treated concurrently (31.0%) and 13.8% occurred after nephrolithiasis. Gender, wheelchair use, bowel segment used, MACE and skeletal fractures were not associated with higher nephrolithiasis risk (p ≥ 0.11). Discussion: This study of a large cohort of SB patients with long-term follow-up highlights that the risk of nephrolithiasis is cumulative and related to bladder stone formation, age at augmentation and time since augmentation. An association with bladder stones suggests potential shared metabolic causes. The study's retrospective design likely led to underestimating the risk of nephrolithiasis by not capturing spontaneously passed stones. Conclusion: Approximately 1% of patients with SB develop nephrolithiasis annually after augmentation. Close long-term surveillance after augmentation is strongly indicated, as nephrolithiasis incidence in augmented patient with SB is at least 10 times higher than general population. Patients with bladder stones are especially at risk. Summary Figure Probability of developing nephrolithiasis in people with spina bifida after bladder augmentation. Summary Figure